2009
DOI: 10.1161/circulationaha.108.812636
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Death and Nonfatal Myocardial Infarction in Acute Coronary Syndrome Patients Receiving Coronary Stenting Are Predicted by Residual Platelet Reactivity to ADP Detected by a Point-of-Care Assay

Abstract: Background-The clinical impact of platelet aggregation assessed by point-of-care assays is unknown. We sought to evaluate whether high residual platelet reactivity (RPR) to ADP during clopidogrel therapy, measured by a point-of-care assay, predicts adverse clinical events in acute coronary syndrome patients undergoing percutaneous coronary intervention. Methods and Results-We used the VerifyNow P2Y12 assay (Accumetrics Inc, San Diego, Calif) to determine RPR to ADP in 683 patients with acute coronary syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
300
7
17

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 499 publications
(345 citation statements)
references
References 24 publications
17
300
7
17
Order By: Relevance
“…patients with stable coronary artery disease (CAD) or unstable angina (UA)/non-ST-segment elevation myocardial infarction (NSTEMI)], but the issue of HTPR of patients needing emergent intervention [i.e. patients with ST-segment elevation myocardial infarction (STEMI)] or patients receiving glycoprotein-blockers has been less intensively investigated (14)(15)(16)(17), although this is a common situation in a "real-life" setting. There is so far no consecutive registry that evaluates the clinical outcome in unselected patients that have been admitted for PCI and coronary stenting with regard to different platelet function tests.…”
Section: Introductionmentioning
confidence: 99%
“…patients with stable coronary artery disease (CAD) or unstable angina (UA)/non-ST-segment elevation myocardial infarction (NSTEMI)], but the issue of HTPR of patients needing emergent intervention [i.e. patients with ST-segment elevation myocardial infarction (STEMI)] or patients receiving glycoprotein-blockers has been less intensively investigated (14)(15)(16)(17), although this is a common situation in a "real-life" setting. There is so far no consecutive registry that evaluates the clinical outcome in unselected patients that have been admitted for PCI and coronary stenting with regard to different platelet function tests.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies indicate high residual platelet reactivity, also referred to as clopidogrel "resistance" or "non-responsiveness", is associated with poor clinical outcomes (1)(2)(3)(4)(5). However, we (6) and others (2) have suggested that a portion of platelet function following treatment with standard dose clopidogrel (300 mg loading dose [LD], 75 mg daily maintenance dose [MD]) is accounted for by pretreatment platelet reactivity -and that clopidogrel "resistance" or "non-responsiveness" may therefore not be appropriate terms.…”
Section: Introductionmentioning
confidence: 99%
“…В литературе накапливается все больше доказательств того, что высокие значения остаточной реактивности тромбоцитов, определенные in vitro у пациентов, получающих ДАТ, сопровождается риском таких нежелательных явлений, как тромбоз стента и смерть от сердечно-сосудистых событий [12,13]. В исследовании RECLOSE [14] у лиц с лабора-торной резистентностью к проводимой ДАТ частота тромбоза стента оказалась значительно выше, чем у больных, чувствительных к АТ.…”
Section: Discussionunclassified